DAMPAK VIRUS COVID 19 DENGAN KEMANDIRIAN BELAJAR ANAK USIA DINI - Susi Herlinda (P3M STKIP 'Aisyiyah Riau, 2022)
Independence is an important thing that must be nurtured from an early age. Children who are not independent can have bad consequences in the future. Educating children through activities during the COVID-19 pandemic whose activities are carried out at home can make students to study independently, assisted by parents at home. There are many activities that students can do during the COVID-19 pandemic, starting from their own activities to teaching materials provided by teachers through their parents. Children's independence will be able to develop when parents and people around them can provide motivation and stimulants so that students will be provoked to carry out their daily activities such as cleaning the bedroom, bathing themselves, doing their own assignments, going to the toilet alone to urinate and defecate. Covid 19 is a virus that spreads in several countries including Indonesia with symptoms of fever, cough and flu to shortness of breath. The impact of this virus initially only had an impact on the economic field, but now it has an impact on the education sector so that learning is carried out using Darring. Learning from home is certainly required by the readiness of students and parents so that learning continues as it should